Understanding the populist voter - Peren K. Arin; Efstathios Polyzos; Marcel Thum (EconPol Forum, 2024)
Left-wing and right-wing populist voters differ the most on the issues of immigration, the importance of traditions, religiosity, and the need to dismantle the welfare state. Populist voters from left and right share concerns about economic insecurity, a lack of empathy by politicians, and a perceived lack of opportunities. They also share a low self-worth and differ in this dimension from non-populist voters Right-wing populist voters have higher identity misperceptions regarding immigration and immigrant groups, while both groups have lower corruption misperceptions compared to non-populist voters.
Keywords: 330